RANCANG BANGUN PEMILAHAN SAMPAH OTOMATIS ORGANIK DAN ANORGANIK MENGGUNAKAN SENSOR MIKROKONTROLER (ARDUINO UNO) - Gde Iwan Setiawan; I Putu Surya Adiputra; Ni Luh Gede Ambaradewi; I Gede Putu Megayasa (Jurnal Manajemen dan Teknologi Informasi, 2026)
Abstract. Technology is currently developing very rapidly. The rapid development of technology in the modern industrial era has resulted in a wide variety of technologies, from newly discovered technologies to technologies that are developments of previous ones. Therefore, this research aims to design and build an automatic waste sorting system based on an Arduino Uno microcontroller, utilizing sensors as the primary tool. This tool is designed using several key components, including an HC-SR04 ultrasonic sensor as a distance detector, a servo used to control the trash bin lid or actuator, and a proximity sensor used to separate organic and inorganic waste. The automatic waste sorting bin has two compartments for organic and inorganic waste and a single entrance for waste disposal. This microcontroller-based trash bin uses a prototype method. The automatic organic and inorganic waste management model uses microcontroller sensors (Arduino Uno) to reduce indiscriminate waste disposal. Test results show that the system can detect and sort waste with a fairly good level of accuracy and fast response times.